Are two beneficial mutations (p.Q249R and 90-bp Indel) within the ovine BMPRIB gene associated with growth traits? - Xu, Hongwei; Akhmet, Nazar; Luo, Yunyun; Guo, Zhenggang; Pan, Chuanying; Song, Enliang; Malmakov, Nurlan; Akhatayeva, Zhanerke; Lan, Xianyong (Frontiers in Veterinary Science, 2024)
Background The problem of achieving economic efficiency in sheep breeding can be largely solved by increasing sheep productivity. Recently, the BMPRIB gene has been revealed by GWAS as a potential candidate gene for sheep body morphometric traits. Therefore, the present study aimed to investigate whether genetic polymorphisms (p.Q249R SNP and 90-bp deletion) in the BMPRIB gene are associated with sheep growth traits. Methods PCR-based genotyping was performed on 1,875 sheep, including 1,191 Guiqian semi-fine wool (GQSFW), 560 Luxi Blackhead (LXBH), 55 Lanzhou fat-tailed (LZFT), and 69 Weining (WN) sheep. Genotype–phenotype association was assessed using the independent samples t-test and ANOVA. The significance level was set at αoriginal < 0.05. The threshold p-value for significance was adjusted after correction for multiple comparisons using the Bonferroni correction. Results After the Bonferroni correction, it was found that individuals with FecB+/FecB+ genotypes of the p.Q249R had significantly better growth traits in LXBH ewe lambs, including the body length, chest width, paunch girth, cannon circumference, and hip width (P<0.0005). Meanwhile, associations were observed between 90-bp deletion polymorphism and several growth traits (body length, body height, chest depth, and canon circumference) in GQSFW ewe adults after the Bonferroni correction (P < 0.0002), and individuals with the “DD” genotypes had greater growth traits. Conclusion Our findings align with the experimental observations from GWAS, which identified the BMPRIB gene as a potential candidate gene for body measurement traits. These findings not only confirm the previous study's results but also expand on them. Therefore, further investigations regarding the impact of BMPRIB polymorphisms on growth traits are necessary in other sheep breeds.